Blaming in the Boom and Bust: Greed Accusations in an Australian Coal Mining Town. Issue 2 (1st September 2019) - Dahlgren, Kari
Abstract : In Australian mining towns like Moranbah, relationships between labour, capital and the state have long been defined by struggles over housing amidst cascading cycles of boom and bust linking global commodity markets to local real estate. Most recently, the emergence of 'fly-in-fly-out' labour arrangements, partially in response to rampant real estate speculation, have challenged mine workers' rights to housing and community. Focusing on the schadenfreude that accompanied the public vilification of one failed, small-time real estate speculator as a case study who is contrasted with the figure of the Cashed-up-Bogan, this article shows how accusations of greed are mobilized to political effect. While greed's tendency to emerge discursively as an accusation might make it seem like an attractive critical discourse, its putative connections to embodiment and the visceral give it an individualizing tendency that allows it to be wielded more easily against persons than institutions, undermining broader structural critiques.